2014
DOI: 10.1074/jbc.m114.558643
|View full text |Cite
|
Sign up to set email alerts
|

YCL047C/POF1 Is a Novel Nicotinamide Mononucleotide Adenylyltransferase (NMNAT) in Saccharomyces cerevisiae

Abstract: Background: Factors regulating NADϩ metabolism and homeostasis remain unclear because of the dynamic nature of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 50 publications
(70 reference statements)
1
35
0
1
Order By: Relevance
“…Supporting this idea, deletions of genes encoding cytosolic nucleotidases Isn1 and Sdt1 (33) significantly decreased NR release (~40 % decrease) (33,162) but only slightly affected intracellular NR level (~15 % decrease) (34,162). Conversely, deleting PHO8 largely decreased intracellular NR level (50–70 % decrease) but only slightly affected the level of NR release (20–30 % decrease) (34,162). To date, the mechanisms of NR uptake and its transport between cellular compartments in higher eukaryotes are still unknown.…”
Section: Intracellular Compartmentalization Of the Nad+ Intermediamentioning
confidence: 89%
“…Supporting this idea, deletions of genes encoding cytosolic nucleotidases Isn1 and Sdt1 (33) significantly decreased NR release (~40 % decrease) (33,162) but only slightly affected intracellular NR level (~15 % decrease) (34,162). Conversely, deleting PHO8 largely decreased intracellular NR level (50–70 % decrease) but only slightly affected the level of NR release (20–30 % decrease) (34,162). To date, the mechanisms of NR uptake and its transport between cellular compartments in higher eukaryotes are still unknown.…”
Section: Intracellular Compartmentalization Of the Nad+ Intermediamentioning
confidence: 89%
“…We previously showed that intracellular NR level largely reflects the NR stored in the vacuole (produced mainly via Pho8) (10). On the other hand, released NR level reflects the NR produced in the cytoplasm (mainly via nucleotidases, Isn1 and Sdt1) (9) because cytoplasmic NR dynamically exchanges with the extracellular environment (4,10,28). It would be interesting to determine whether other NR homeostasis factors, such as Isn1 and Sdt1, also play a role in ssy5⌬-mediated NR salvaging.…”
Section: Discussionmentioning
confidence: 99%
“…For each qPCR reaction, 50 ng of cDNA and 500 nM concentrations of each primer were used. qPCR reaction was run on Roche LightCycler 480 using LightCycler 480 SYBR Green I Master Mix (Roche Applied Science) as previously described (28). Average size of the amplicon for each gene was ϳ150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…This screen system was based on our observations that yeast cells release and transport NR back into the cell (19), a phenomenon that is also conserved in human cells (20). Our studies have identified novel NAD + homeostasis factors including the phosphate responsive signaling (PHO) pathway (17), the SPS amino acid sensing pathway (21), a conserved vacuolar NR transporter Fun26 (1,17) and several NAD + metabolic enzymes (22).…”
mentioning
confidence: 99%